2011
DOI: 10.2223/jped.2069
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory disease screening in school-aged children using portable spirometry

Abstract: Objectives: To assess the prevalence of respiratory disease in schoolaged children and to determine the value of field spirometry.Methods: Data on 313 1st and 4th graders from four public schools in Lisbon were analyzed. A respiratory self-answered questionnaire and standard spirometry were performed. Descriptive and bivariate analysis was followed by multiple logistic regression.Results: Thirty-five percent of the children presented at least one episode of wheezing (18% ≥ 2 episodes), and 4% had asthma. Wheez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…A total of 70 children were enrolled in the study; of which 35 cases were in the recurrent RP group and 35 cases in the no-recurrent RP group. The median age of presentation in years in the two groups was 10 [6-13] and 12 [8][9][10][11][12][13] respectively. Male: female ratio in the recurrent RP group was 1.91:1 while in no recurrent RP group it was 1.18:1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 70 children were enrolled in the study; of which 35 cases were in the recurrent RP group and 35 cases in the no-recurrent RP group. The median age of presentation in years in the two groups was 10 [6-13] and 12 [8][9][10][11][12][13] respectively. Male: female ratio in the recurrent RP group was 1.91:1 while in no recurrent RP group it was 1.18:1.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study of its kind conducted in our part of the world. Spirometry has been used in the management of children with bronchial asthma for some time now 12,21,23,25,26 . Several studies have shown that derangements in lung function parameters can also be seen in bronchiolitis obliterans, bronchiectasis (cystic fibrosis-associated or otherwise), hemoglobin disorders like sickle cell disease, etc 14,15,18,27,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association we found between the presence of respiratory symptoms and abnormal spirometry in children has been previously reported. 6,19,32 This is important because it suggests that the presence of cough precipitated by dust, and wheeze in children should serve as a prompt for screening spirometry to exclude abnormal patterns which could be either obstructive or restrictive. Failure to identify abnormal spirometry pattern in children is a missed opportunity for early intervention to improve both short term and long outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation increases morbidity and mortality amongst children, with recognized negative impact on long term outcomes in adulthood. 3,[6][7][8][9][10] Recognition of impaired lung function in childhood may be an opportunity for a potentially effective intervention, such as early referral for specialized care with prompt treatment. 2,[7][8][9] Optimizing lung function in childhood is thus an important public health priority.…”
Section: Introductionmentioning
confidence: 99%